2005
DOI: 10.1177/107769900508200304
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Matters: A Cross-Market Assessment of Newspaper Error and Credibility

Abstract: A survey of 4,800 news sources cited in fourteen newspapers provides a cross-market assessment of newspaper accuracy and the effect of errors on newspaper credibility. Sources found errors in 61% of local news and feature stories, an inaccuracy rate among the highest reported in nearly seventy years of accuracy research. Newspaper credibility, as perceived by news sources, significantly declined in relation to frequency and severity of errors. Inaccuracy negatively affected source willingness to cooperate with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 15 publications
0
71
0
5
Order By: Relevance
“…In the largest and most recent accuracy study, three out of five news stories published in American regional newspapers were found to contain at least one error -an inaccuracy rate among the highest reported (Meyer 2004;Maier 2005). In separate analyses, 1 Meyer and Maier showed that inaccuracy influenced source perceptions of newspaper credibility.…”
Section: Observesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the largest and most recent accuracy study, three out of five news stories published in American regional newspapers were found to contain at least one error -an inaccuracy rate among the highest reported (Meyer 2004;Maier 2005). In separate analyses, 1 Meyer and Maier showed that inaccuracy influenced source perceptions of newspaper credibility.…”
Section: Observesmentioning
confidence: 99%
“…To compare newspaper accuracy in Switzerland and Italy to longitudinal accuracy research in the United States, the study closely followed the methodology pioneered by Charnley (1936) and adapted by Maier (2005). As part of a larger investigation of media quality and profitability (Meyer, 2004), Maier's U.S. news accuracy study included a cross-section of 14 newspapers 2 in markets with existing data on local trust in newspapers available from the Knight Foundation community surveys.…”
Section: Sampling and Instrumentmentioning
confidence: 99%
“…Evers destaca que cuando se habla de temas de calidad -professional ethics inevitably is a stake, as the concept of ‗journalistic quality' contains a number of normative notions as well: reliability, credibility, accuracy and responsibility‖ (2012: 226). La correlación entre calidad y credibilidad ha sido destacada por distintos investigadores (Hovland y Weiss, 1951;Schatz y Schulz, 1992;Russ-Mohl, 1994;Metzger et al, 2003;Maier, 2005) y sus efectos confirmados por estudios recientes del Pew Research Center, que destacan que los medios no son una excepción en la ecuación que vincula pérdida de calidad y deserción de los lectores de un medio (Enda y Mitchell, 2013).…”
Section: Estado De La Cuestión: El 'Ombudsman' Como Garantía De Calidadunclassified
“…11 Em pesquisa posterior, Maier (2005) Nesta análise de conteúdo, busco verificar a frequência de informações quantitativas em um veículo jornalístico brasileiro. Ela avança em relações aos trabalhos anteriores identificando os tipos de conhecimento matemático e estatístico relacionado a cada ocorrência de informação quantitativa encontrada em reportagens jornalísticas.…”
Section: Conceitualização E Propósitounclassified
“…Para jornalistas, as consequências das dificuldades com números não se limitam a erros -como os documentados nos estudos de Maier (2002, 2005) e Brand (2008. Esses profissionais também precisam de grau sofisticado de literacia matemática para compreender e avaliar fatos nas notícias, principalmente no trabalho com probabilidade, pesquisas, amostragem e estatística (Steen, 2001).…”
Section: Currículo Teoria E Práticaunclassified